Coaxial‐electrospinning as a new method to study confined crystallization of polymer. Issue 5 (4th December 2012) - Luo, Hongjun; Huang, Yong; Wang, Dongshan; Shi, Jun
Abstract Coaxial‐electrospinning (ES) was used as a new method to fabricate one‐dimensional (1D) confinements for studying confined crystallization of poly(ethylene glycol) (PEG). A series of core–sheath ultrafine fibers with PEG as the core and cellulose acetate as the sheath were obtained by coaxial ES. It was found that the uniform core–sheath ultrafine fibers could be fabricated and a (1D) confinement environment, a nanotube with a diameter from 68 to 860 nm, could be obtained by coaxial‐ES. When the confinement dimension decreased to be smaller than 120 nm in diameter, the melt temperature (Tm), the crystallization temperature (Tc), the crystallinity (Xm), and the crystal sizes of the PEG were much smaller than those of bulk PEG and when the nanotube was larger than 200 nm in diameter, the Tm, Tc, Xm, and the crystallite sizes of the PEG were close to those of bulk PEG, which suggested that the crystallization of the PEG was influenced by the confinement dimension. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013